Sorafenib improves alkylating therapy by blocking induced inflammation, invasion and angiogenesis in breast cancer cells. (1st July 2018) - Zanotto-Filho, Alfeu; Rajamanickam, Subapriya; Loranc, Eva; Masamsetti, V. Pragathi; Gorthi, Aparna; Romero, July Carolina; Tonapi, Sonal; Gonçalves, Rosangela Mayer; Reddick, Robert L.; Benavides, Raymond; Kuhn, John; Chen, Yidong; et al.
Abstract: Molecular targeted compounds are emerging as a strategy to improve classical chemotherapy. Herein, we describe that using low dose of the multikinase inhibitor sorafenib improves cyclophosphamide antitumor activity by inhibiting angiogenesis, metastasis and promoting tumor healing in MDA-MB231 xenografts and the 4T1-12B syngeneic breast cancer metastasis model. Mechanistic studies in MDA-MB231 cells revealed that alkylation upregulates inflammatory genes/proteins such as COX-2, IL8, CXCL2 and MMP1 in a MEK1/2-ERK1/2-dependent manner. These proteins enrich the secretome of cancer cells, stimulating cell invasion and angiogenesis via autocrine and paracrine mechanisms. Sorafenib inhibits MEK1/2-ERK1/2 pathway thereby decreasing inflammatory genes and mitigating cell invasion and angiogenesis at basal and alkylation-induced conditions whereas NRF2 and ER stress pathways involved in alkylation survival are not affected. In non-invasive/non-angiogenic breast cancer cells (SKBR3 and MCF7), alkylation did not elicit inflammatory responses with the only sorafenib effect being ERK1/2-independent ROS-dependent cytotoxicity when using higher drug concentrations. In summary, our data show that alkylating agents may elicit inflammatory responses that seems to contribute to malignant progression in specific breast cancer cells. Identifying and targeting drivers of this phenotype may offer opportunities to optimize combined drug regimens between classical chemotherapeutics and targeted agents. Highlights: Inflammatory secretome from cancer cells augments cell invasion and angiogenesis. Inflammatory gene expression is dependent upon MEK1/2-ERK1/2 pathway activation. Alkylating agent induces inflammatory gene expression in vitro and in xenografts. Sorafenib blocks MEK1/2-ERK1/2, inhibits inflammation, invasion and angiogenesis. Sorafenib inhibits tumor inflammation and improves alkylation therapy in mice models.